Avellino und Benevent, Italien: Rekontextualisierung römischer Skulptur im antiken Hirpinien - Nowak, Christiane (e-Forschungsberichte des DAI, 2023)
This project aims to investigate an hitherto unknown part of roman Italy, ancient Irpinia, based on the remains of roman sculpture.